Selected Lectures of the 16th International Workshop on Neonatology, Virtual Edition; Cagliari (Italy); October 29th-30th, 2020 - - (Hygeia Press di Corridori Marinella, 2020)
Selected Lectures of the 16th International Workshop on Neonatology • Virtual Edition • NEONATOLOGY: STEPS TOWARDS THE FUTURE IN THE COVID-19 ERA • Cagliari (Italy) • October 29th-30th, 2020   LECT 1 • Neonatal ventilation in the third millennium • C. Moretti, C. Gizzi (Rome, Italy) LECT 2 • COVID-19 in children: what did we learn? • M. Votto, R. Castagnoli, I. Brambilla, A. Licari, G.L. Marseglia (Pavia, Italy) LECT 3 • COVID-19, microbiota and lung-gut axis • V. Fanos, M.C. Pintus, M.A. Marcialis, R. Pintus (Cagliari, Italy) LECT 4 • Enteral nutrition for very preterm infants: the facts, the assumptions and the unknowns • B.W. Kramer (Maastricht, The Netherlands) LECT 5 • Lactoferrin in the prevention of viral infections: from molecular mechanisms to clinical implications • D. Peroni, G. Costagliola, E. Spada (Pisa, Italy) LECT 6 • Neonatal sepsis: present and future • K. Sarafidis (Thessaloniki, Greece) LECT 7 • The Neonatology after COVID-19 • F. Mosca, M. Fumagalli, P. Schiavolin, C. Pietrasanta, A. Ronchi, L. Pugni (Milan, Italy) LECT 8 • The development of immunity, from fetal life to newborn: where health begins • C. Salpietro, G. Ceravolo, C. Cuppari (Messina, Italy)